Plasmids can transfer to Clostridium difficile CD37 and 630Δerm both by a DNase resistant conjugation-like mechanism and a DNase sensitive mechanism. Issue 21 (4th October 2017) - Khodadoost, Ladan; Hussain, Haitham; Mullany, Peter
Abstract: Broad host range conjugative plasmids that replicate in Escherichia coli have been widely used to mobilise smaller replicons, bearing their cognate origin of transfer ( oriT ) into a variety of organisms that are less tractable genetically, such as Clostridium (Clostridioides) difficile . In this work we demonstrated that the oriT region of pMTL9301 (derived from RK2) is not required for transfer between E. coli and C. difficile strains 630Δ erm and CD37 and that this oriT -independent transfer is abolished in the presence of DNase when CD37 is the recipient. Transfer to the 630Δ erm strain is DNase resistant even without an obvious oriT, when E. coli CA434 is used as a donor and is sensitive to DNase when E. coli HB101 is the donor. Abstract : Clostridium difficile can acquire DNA from its environment, allowing it to rapidly respond to environmental change.